Model Penyelenggaraan Pendidikan Inklusif bagi Penyandang Disabilitas Intelektual: Studi Kasus di DKI Jakarta - Emilia Kristiyanti (Indonesian Center for Religion and Society Studies (InTReSt), 2019)
This study aims to develop a model for the implementation of inclusive education for people with intellectual disabilities in DKI Jakarta. As a region that has local regulations on the protection of persons with disabilities, DKI Jakarta government has not yet been able to ensure the fulfillment of the education rights of children with intellectual disabilities. This study used a single instrumental case study approach and was carried out in DKI Jakarta. Data collection is done through in-depth interviews and textual analysis. The results show that social exclusion occurs because of cultural barriers due to stigma, labeling, prejudice, stereotypes, and structural barriers due to discriminatory policies. Both of barriers can be reduced by organizing inclusive education for persons with intellectual disabilities. The model for implementing inclusive education developed not only focuses on developing the life skills of individuals with intellectual disabilities, but also strengthening and developing the surrounding environment and society. Thus, children with intellectual disabilities can be independent and participate in society.